2020
DOI: 10.1093/nutrit/nuaa122
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding and future health in Mexico. Introduction to the XI Nestlé Nutrition Conference

Abstract: Nutrition in infancy provides an important window of opportunity to shape good health during childhood and adult life. The objective of this manuscript is to provide an introduction to the review articles that bring together the proceedings of the XI Nestlé Nutrition Conference “Complementary Feeding: A Piece of the Puzzle to Understand Future Health”. The studies and description of complementary feeding practices in Mexico, from the Mexican National Health and Nutrition Survey 2012 (ENSANUT 2012), support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…and by the year of 2018, a recovery of all breastfeeding indicators was reported, with a prevalence of 28.6% for exclusive breastfeeding. 15 Exclusive breastfeeding is defined as the practice of only feeding breast milk to an infant for the first 6 months of life (without the addition of any other type of food or water); such practice has the greatest potential impact on infant mortality than any other prevention intervention. Similarly, other practices that contribute in the adequacy of optimal breastfeeding are initiation of breastfeeding within the first hour of life and continuation of breastfeeding until 2 years of age or as far as possible beyond.…”
Section: Breastfeeding In México: a General Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…and by the year of 2018, a recovery of all breastfeeding indicators was reported, with a prevalence of 28.6% for exclusive breastfeeding. 15 Exclusive breastfeeding is defined as the practice of only feeding breast milk to an infant for the first 6 months of life (without the addition of any other type of food or water); such practice has the greatest potential impact on infant mortality than any other prevention intervention. Similarly, other practices that contribute in the adequacy of optimal breastfeeding are initiation of breastfeeding within the first hour of life and continuation of breastfeeding until 2 years of age or as far as possible beyond.…”
Section: Breastfeeding In México: a General Overviewmentioning
confidence: 99%
“…Breastfeeding seems to be implemented along with the introduction of infant formula and/or other types of milk. 15 A recent analysis of breastfeeding protection, promotion and support systems in Mexico; the results of which showed that physicians and nursing professionals in primary care clinics in Mexico had a low baseline knowledge and skills base to promote and support breastfeeding. Which highlights the need for in-service training to improve breastfeeding knowledge and skills in health professionals.…”
Section: Breastfeeding In México: a General Overviewmentioning
confidence: 99%
See 1 more Smart Citation